(untitled) (Journal of science and technology exploration, 2025)
As the global automotive industry accelerates its"data-driven"transformation, intelligent automakers face challenges in effectively leveraging massive data assets through traditional methods. AI data mining has emerged as a critical breakthrough. This paper explores the application of AI data mining technologies in smart automotive enterprises, proposing key technologies (data preprocessing, machine learning, deep learning), comprehensive value chain planning (R&D, design, production, operations, services, user engagement), and practical implementations (BYD’s end-to-end data applications, NVIDIA security solutions). It summarizes core AI data mining technologies (data security, algorithm stability, talent development) and corresponding strategies. Through strategic planning and practical applications of AI data mining, this study drives the"data assetization"of intelligent automakers, providing valuable insights for the industry’s intelligent transformation.